A model of scientific communication as a global distributed information system - Bo-Christer Bjork (Information Research: An International Electronic Journal)
Introduction. A formal graphical model of the scientific communication process is presented in this paper. Purpose. The purpose of the model is to act as a road map for policy discussions and research concerning the process. In comparison to earlier models found in the literature this model is more detailed, hierarchical and includes more modelling constructs (activities, inputs, outputs, controls, mechanisms). Method. logy. The modelling methodology used is IDEF0, a process modelling method, which previously has mainly been used for business process reengineering in the manufacturing industry. The current version of the model consists of thirty-three diagrams, with 113 different activities and over 200 different inputs, outputs, controls and mechanisms. Scope. The scope of the model is the whole communication value chain, from initial research to the assimilation of research results to improve every-day life. The model treats both informal and formal communication, as well as the publishing of data, but the major focus is on modelling the publishing and indexing of traditional peer reviewed journal articles, as well as the activities of readers to find out about them and access them. The new business models and parallel functions enabled by the Internet, such as open access journals and e-print repositories, are also in focus.